Economic Integration in Asia Towards the Delineation of a Sustainable Path - Andreosso-O'Callaghan, B.; Jaussaud, J.; Zolin, B.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Pivot, 2014)
This study assesses the current state of economic integration in Asia - in particular in East and South East Asia- and analyzes the prerequisites for a sustainable path of economic integration, using the background of the EU experience as a benchmark.
Keywords: Asia—Economic conditions; International economics; Economic policy; Development economics; Economic growth; Asian Economics; International Economics; Economic Policy; Development Economics; Economic Growth